Pengaruh Electronic Word of Mouth pada Media Sosial Instagram Terhadap Keputusan Berkunjung - Dian Pangestuti; Sigit Wibawanto (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi, 2021)
This study aims to examine and analyze the effect of electronic word of mouth on the decision to visit Rahayu River Tubing Padureso. Sampling used a non probability sampling method with purpoave sampling technique, namely a sampling technique with certain considerations, this study took a sample of 120 respondents to visitors to Rahayu River Tubing Padureso with 117 respondents who met the criteria and data analysis could be done. This research is a type of quantitative research. Data collection techniques were carried out using a questionnaire The data analyas tool uses the help of a computer application program, namely IBM SPSS Statistics 25 which includes Instrument Validity and Reliability Test, Classical Assumption Test, Multiple Regression Analysis, and Hypothesis Testing The results of this study indicate that all variables are valid and reliable, there is no multicollinearity, there is no heteroscedasticity, and fulfills the assumption of nonnality. Based on the results of the partial test, it was found that the intensity variable had no significant effect on viating decisions, but the valence of pontive opinion and content variables had a significant effect onvisiting decisions Simultaneous test results show that this study has a significant effect together with the Fcount value of 44,736. The results of the coefficient of determination in this study were 54.3%, the decision vanable to visit Rahayu River Tubing Padureso was influenced by the intensity, valence of positive opinion and content vanables, while the remaining 45:2% could be explained by other vanables.